Dinding Rapuh Pelindungan Korban Kekerasan Seksual Berbasis Digital - Nurtjahyo, Lidwina Inge (Yayasan Jurnal Perempuan, 2024)
Despite Indonesia has enacted the Anti-Sexual Violence Law, cases of sexual violence on social media platforms continue to occur and are not easy to resolve. There are problems in implementing regulations in the digital space: criminalization of the victim, regulations that do not accommodate women’s experiences, and the issue of evidence. This article discusses digital sexual violence cases, focus on the non-consensual sharing of intimate content and trespassing of private spaces. How regulations are still unable to provide a safe space in the digital sphere. This article is based on literature research including analysis of regulations, court verdict, and some news about sexual violence in digital sphere. The author uses a feminist legal studies perspective in the analysis